Thermodynamic analysis of MgxFe3‐xO4 redox CO2 conversion solar thermochemical cycle - Rahul R. Bhosale (6467102) (2023)
The solar-to-fuel energy conversion efficiency (ɳsolar-to-fuel) of the MgxFe3-xO4 (x = 0.2-1.0) based CO2 splitting (CDS) cycle is estimated at steady reduction (Tred) and oxidation temperatures (Toxd) equal to 1673 K and 1273 K, respectively. The efficiency analysis is performed using the experimental results reported in the sol-gel-derived MgxFe3-xO4 based CDS cycle. The redox nonstoichiometry allied with the MgxFe3-xO4 during the reduction (δred) and oxidation steps (δoxd) is determined based on the experimentally obtained results. Efficiency analysis is conducted by considering the heat energy required to heat inert sweep gas and CO2. Heat penalty allied with the separation of the inert sweep gas from O2 and CO2 from CO is also considered. The solid-to-solid heat recovery effectiveness (Ɛss) is assumed to be zero, whereas the gas-to-gas heat recovery effectiveness (Ɛgg) kept steady at 0.5. The release of a high amount of O2 and the production of an elevated CO level is responsible for the rise in the energy penalty associated with both separators. The obtained results also indicate that the total thermal energy required (Q̇MgF-TC) to drive the cycle depends heavily on the sensible heat required (Q̇MgF-sens) for raising the temperature of MgxFe3-xO4 from Toxd to Tred. The obtained results also show that ɳsolar-to-fuel depends heavily on the amount of CO produced and hence recorded to be the highest (4.3%) in the case of MgFe2O4. Other Information Published in: International Journal of Energy Research License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.1002/er.7213